2020
DOI: 10.3390/met10060743
|View full text |Cite
|
Sign up to set email alerts
|

Friction-Induced Martensitic Transformation and Wear Properties of Stainless Steel under Dry and Wet Conditions

Abstract: The wear characteristics of SUS304 and SUS316 stainless steels were evaluated at the rotation speeds of 100 m/s, 200 m/s, and 300 m/s under dry and wet conditions. The transition of friction-induced martensite occurred in wear-affected regions of two materials, regardless of the wear test conditions. The specific wear rates (Ws) of both stainless steels increase with increasing rotation speeds, regardless of the circumstances. Moreover, Ws of SUS304 and SUS316, obtained under dry conditions, is significantly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Figure 9d shows the X-ray diffractogram of the HIP + HT material after tribological testing. It should be noted that after testing, martensite (α') is observed on the surface of the HIP + HT sample, probably due to the strain-induced martensitic transformation of austenitic stainless steels caused by excessive plastic deformation [29]. Interestingly, this transformation was not observed for the as-HIP sample.…”
Section: Tribology Testingmentioning
confidence: 96%
See 1 more Smart Citation
“…Figure 9d shows the X-ray diffractogram of the HIP + HT material after tribological testing. It should be noted that after testing, martensite (α') is observed on the surface of the HIP + HT sample, probably due to the strain-induced martensitic transformation of austenitic stainless steels caused by excessive plastic deformation [29]. Interestingly, this transformation was not observed for the as-HIP sample.…”
Section: Tribology Testingmentioning
confidence: 96%
“…Small changes in the friction coefficient of the HIP sample during the test may be caused by the contact instability when the indenter ploughed against the samples [29,30]. Qiao et al [14] reported that, for nickel-free stainless steel Fe-19Cr-15Mn-0.66N (in wt.…”
Section: Tribology Testingmentioning
confidence: 99%